Praktek Transaksi Pada Koperasi Karyawan Daerah Kota Surakarta Dalam Tinjauan Hukum Islam dan Tingkat Pemahaman Anggotanya Dalam Hal Riba - Muhamad; Rochmat Budi Santoso (TAFAQQUH, 2021)
This study aims to determine what transaction practices are carried out by the Surakarta City Employee Cooperative (Kokarda) and how these practices are in the view of Islamic law. In addition, this study aims to reveal how far the members of the cooperative, who are mostly Muslims, understand about usury. The technique of collecting data from literature books or data published by the Regional Employee Cooperative (Kokarda) in Surakarta is used to obtain data in literature. To support the research, data collection using a questionnaire, then analyzed quantitatively and descriptively. The questionnaire consists of questions about the respondent's knowledge of the application of the interest system, the purpose of saving or saving money and the respondents' interest in borrowing in the cooperative. Researchers also developed in the form of random interviews with some respondents. The results showed that the Surakarta Regional Employee Cooperative (Kokarda) implemented savings and loan transactions. Saving money in the cooperative earns interest on deposits. Borrowers of money are required to pay interest on the loan. The members, who are mostly Muslims, have a high enough interest in saving and borrowing money from the cooperative.